Nutritional and exercise-related determinants of bone density in elite female runners. - Gibson, J; Mitchell, A; Harries, MG; Reeve, J (2004)
Although the female athletic triad is widely recognized clinically, there have been few studies quantitating the effect of disordered eating on bone mineral density. The purpose of this study was to explore the mechanisms through which disordered eating might influence the skeleton in nationally or internationally competitive runners. Fifty British national or higher standard middle and long-distance female runners aged under 36 years were recruited; 24 had amenorrhea (AM), nine had oligomenorrhea (OL) and the others were eumenorrheic (EU). Bone mineral density (BMD g.cm(-2)) of the proximal femur (femoral neck and trochanter) and lumbar spine (L2-L4) was measured by dual energy X-ray absorptiometry (DXA) and compared with population-based European reference data. Dietary eating patterns were assessed with the Eating Attitudes Test (EAT26) and Bulimia Investigatory Test Edinburgh (BITE) questionnaires. High eating disorder scores were common; the EAT26 score predicted menstrual disorders (P=0.014) and correlated with body mass index (BMI). BMD was generally low in the AM group, but was raised in the proximal femur in the EU group. In the AM group, younger age at start of training was associated with higher trochanteric BMD. In addition, years of eumenorrhea were positively associated with spine BMD. Although a high EAT26 score was associated with lower BMD in the proximal femur, this could be explained by the intermediary effect of menstrual disorders. Osteocalcin, a marker of bone formation, was reduced in the AM group and was also reduced by high VO2max and high BITE score, consistent with a central (hypothalamic) pathway for suppressing osteoblastic bone formation. Eumenorrheic runners had increased femoral BMD compared with European controls, consistent with a positive effect of increased mechanical loading. The effect of disordered eating to reduce BMD could be explained by its association with menstrual dysfunction. Lumbar spine BMD was reduced most in those athletes who menstruated for the shortest time in adolescence.